Clinical Inquiries: Do preparticipation physical exams reduce morbidity and mortality for athletes? - Hulkower, Stephen; Fagan, Blake; Watts, Jana; Ketterman, Elizabeth (East Carolina University, 2005)
This article reviews research to determine if preparticipation physical exams reduce morbidity and mortality for athletes.
Do preparticipation physical exams reduce morbidity and mortality for athletes?
Keywords: Sudden death; Asthma; Heart attacks; Congenital defects; Athletes; Athletic exams; Sports; Sports medicine